2022
DOI: 10.1371/journal.pone.0263177
|View full text |Cite
|
Sign up to set email alerts
|

Loot box engagement: A scoping review of primary studies on prevalence and association with problematic gaming and gambling

Abstract: Background Loot boxes are an increasingly common type of random microtransaction in videogames. There is some concern about their expansion and entailed risks, especially among adolescents. The actual prevalence of engagement with loot boxes among child and adult population is uncertain, and there is still controversy over the nature of their relationship with problematic gaming and gambling. Objectives The aims of this scoping review are to summarize the characteristics and findings of published primary emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 53 publications
0
26
1
4
Order By: Relevance
“…Moreover, there was no correlation between purchasing loot boxes in the last 4 weeks and age, indicating that younger adolescents may be no less likely to engage in this activity. Previous studies have found higher annual prevalence of loot box purchasing amongst adult gamers compared to adolescent gamers, but the reverse finding in general population studies ( Montiel et al, 2022 ). Our results suggest that adolescents aged 12–17 years may be similar in their level of loot box engagement.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Moreover, there was no correlation between purchasing loot boxes in the last 4 weeks and age, indicating that younger adolescents may be no less likely to engage in this activity. Previous studies have found higher annual prevalence of loot box purchasing amongst adult gamers compared to adolescent gamers, but the reverse finding in general population studies ( Montiel et al, 2022 ). Our results suggest that adolescents aged 12–17 years may be similar in their level of loot box engagement.…”
Section: Discussionmentioning
confidence: 76%
“…Of key concern is the link between loot box purchasing and problem gambling. All 16 studies reviewed in a recent scoping study corroborated this relationship ( Montiel, Basterra-González, Machimbarrena, Ortega-Barón, & González-Cabrera, 2022 ). Two meta-analyses of 13 studies ( Spicer et al, 2021 ) and 15 studies ( Garea, Drummond, Sauer, Hall, & Williams, 2021 ) found significant small-to-moderate, but clinically relevant, positive correlations of 0.27 and 0.26, respectively, between loot box spending and problem gambling symptomatology.…”
Section: Introductionmentioning
confidence: 83%
“…Importantly, loot box expenditure has been found to be positively correlated with self-reported problem gambling severity in many cross-sectional studies across various Western countries, including the USA [37], Spain [38], Denmark [39] and Australia [40], amongst both adult and adolescent player samples [41]. Reviews and meta-analyses of these studies have been conducted elsewhere [42••]; [43][44][45]. However, the causal direction (if any) of this positive correlation is not known [46], and there is debate as to how the current evidence base should be interpreted.…”
Section: Differing Interpretations Of the Loot Box 'Harm' Evidence Ba...mentioning
confidence: 99%
“…In many Western countries, loot box expenditure has been repeatedly found to be positively correlated with problem gambling severity (Garea et al 2021;Spicer et al 2021;Yokomitsu et al 2021;Montiel et al 2022). This relationship has been relied upon by policymakers to evince the potential harms of loot boxes(Digital, Culture, Media and Sport Committee of the House of Commons (UK) 2019, paras82-86; Select Committee on the Social and Economic Impact of the Gambling Industry of the House of Lords (UK) 2020, paras432-436).…”
Section: The Oft-cited Positive Correlation: Has Loot Box 'Harm' Trul...mentioning
confidence: 99%